2013
DOI: 10.1186/1471-2350-14-91
|View full text |Cite
|
Sign up to set email alerts
|

Splice site SNPs of phospholipase PLCXD3 are significantly associated with variant and sporadic Creutzfeldt-Jakob disease

Abstract: BackgroundVariant Creutzfeldt-Jakob disease is an infectious, neurodegenerative, protein-misfolding disease, of the prion disease family, originally acquired through ingestion of meat products contaminated with bovine spongiform encephalopathy (BSE). Public health concern was increased by the discovery of human-to-human transmission via blood transfusion. This study has verified a novel genetic marker linked to disease risk.MethodsSNP imputation and association testing indicated those genes that had significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
0
9
1
1
Order By: Relevance
“…We calculated p -values of association for all SNPs located within PLCXD3 and within 50 kilobases of the gene, including for the three SNPs sequenced in the previous study, rs545358, rs319013 and rs76547469, the former two of which were reported as having allele and genotype frequencies significantly different to publicly available European control populations [ 4 ] using SNPTESTv2.5β [ 5 ]. As genotype data in our GWAS was imputed we confirmed that imputation was accurate with both allele discrimination PCR probes and Sanger sequencing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We calculated p -values of association for all SNPs located within PLCXD3 and within 50 kilobases of the gene, including for the three SNPs sequenced in the previous study, rs545358, rs319013 and rs76547469, the former two of which were reported as having allele and genotype frequencies significantly different to publicly available European control populations [ 4 ] using SNPTESTv2.5β [ 5 ]. As genotype data in our GWAS was imputed we confirmed that imputation was accurate with both allele discrimination PCR probes and Sanger sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Recently a re-analysis of a previously published GWAS [ 3 ] consisting of 85 vCJD cases and 1481 control individuals found that after PRNP , the region most significantly associated with disease was at the PLCXD3 gene locus. Resequencing three intronic SNPs near the splice junction of intron 1 and exon 2 of this gene in 109 sCJD and 120 vCJD cases revealed that two of these SNPs showed marked Hardy-Weinberg disequilibrium and were highly significantly associated with disease compared to publicly available controls [ 4 ]. As this effect was extremely strong, we sought to replicate the finding in a further cohort of human prion disease cases to find out whether this gene was associated with increased disease risk and investigate any effects on clinical phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a polymorphism that alters the protease activ-575 ity of cathepsin D, an enzyme with a proposed role in the metabo-576 lism of amyloid-beta peptide, was associated with increased risk 577 for vCJD in a small part of the population(Bishop et al, 2008). Thus, 578 as suggested by a recent additional study(Bishop et al, 2013), it 579 seems probable that in addition to the major effect of codon 129580 polymorphism within PRNP, other loci might modulate at a minor 581 level the susceptibility to vCJD. 582 It is unclear whether the protective barrier of transmission 583 towards vCJD provided by VV and MV genotypes at codon 129 is 584 complete and whether we would observed secondary waves of 585 vCJD with longer incubation period.…”
mentioning
confidence: 87%
“…Intron region polymorphism in ULK1 associate with decreased expression of the gene, compromised immune responses and associate with increase M.tb replication in the latently infected patients leading to the development of pulmonary TB ( 33 ). The SNPs in the splice sites of PLCXD3 showed significant association with prion mediated sporadic Creutzfeldt-Jakob's Disease ( 34 ).…”
Section: Splicingmentioning
confidence: 99%